The effect of Kinesiology Taping on spinal motion and physiological spinal curvatures. A literature review - Grześkowiak, Marcin; Szulc, Paweł; Szwedziak, Marek; Lewandowski, Jacek (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The Kinesiology Taping/Kinesio Taping (KT) method has become more and more popular in recent years. Many studies have demonstrated the application of this method in numerous fields of medicine. Despite its continuous development, several issues pertaining to the legitimacy of application and operation mechanisms of KT still need to be addressed. Aim of Study. The article is a review of literature in regarding the effects of KT on spinal motion and physiological spinal curvatures. Material and Methods. This study is based on an analysis of databases such as SPORTDiscus, Medline, ScienceDirect, EBSCOhost and Google Scholar. Results. Seven research articles corresponding to the aim of this study have been found. Four of those articles are devoted to the lumbar spinal segment, two discuss the motion of the cervical spinal segment, and one concentrates on lumbar lordosis. None of the articles included information on any negative effects of KT. Conclusions. The effect of KT on the assessed parameters is barely noticeable. Therefore, it is necessary to conduct further research regarding effects of the Kinesiology Taping method on spinal motion and physiological spinal curvatures
Keywords: Kinesio Taping; Kinesiology Taping; spinalmotion; spinal curvatures